Allogeneic Transplant Physician and Center Capacity in the United States - Majhail, Navneet S (2011)
Shortage of manpower and center capacity is expected to be a major challenge to the anticipated future growth in the utilization of allogeneic hematopoietic-cell transplantation (HCT) in the United States (US). Using data from the National Marrow Donor Program's Transplant Center Network Renewal Survey, we describe transplant center and transplant physician capacity in the US from 2005 to 2009. Over this five year period, the number of allogeneic transplants increased by 30%, bed capacity increased by 17% and physician full time equivalents increased by 26%. The number of related donor HCT increased by 15% and unrelated donor HCT increased by 45%. In addition to large centers, small and medium sized centers also made a major contribution to overall national transplant volumes for both related and unrelated donor HCT. Increase in utilization of unrelated donor HCT occurred in centers irrespective of their size. The majority of transplant centers were performing more transplants using existing physician and bed capacity. Our study provides important description of allogeneic transplant activity and capacity of US centers and our data will assist policy makers plan for the projected growth in the use of transplantation.